2001
DOI: 10.1029/2000gl012685
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for charged aerosols and associated meter‐scale structure in identified PMSE/NLC regions

Abstract: While we have conducted previous rocket investigations of NLC/PMSE ion properties, the DROPPS payloads provided the first opportunity to fly a complete complement of our probe systems for simultaneously evaluating the region's electrical structure as well as the presence of charged aerosols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 7 publications
8
30
0
Order By: Relevance
“…These measurements are however much more difficult to explain than the observations of negatively charged particles. In subsequent campaigns, several investigations have provided further evidence for the existence of negatively charged aerosol particles in PMSE (Havnes et al, 2001;Mitchell et al, 2001Mitchell et al, , 2003Smiley et al, 2003). Concerning positively charged particles there seem to be further indications that they do exist (Mitchell et al, , 2003Smiley et al, 2003), however, our current understanding of these measurements is far from being conclusive.…”
Section: Observation Of Charged Ice Particlesmentioning
confidence: 90%
“…These measurements are however much more difficult to explain than the observations of negatively charged particles. In subsequent campaigns, several investigations have provided further evidence for the existence of negatively charged aerosol particles in PMSE (Havnes et al, 2001;Mitchell et al, 2001Mitchell et al, , 2003Smiley et al, 2003). Concerning positively charged particles there seem to be further indications that they do exist (Mitchell et al, , 2003Smiley et al, 2003), however, our current understanding of these measurements is far from being conclusive.…”
Section: Observation Of Charged Ice Particlesmentioning
confidence: 90%
“…The dust was not observed visually or by lidars but a strong PMSE layer was present. Later, rocket probe observations (Mitchell et al, 2001;Havnes et al, 2001a, b;Smiley et al, 2006) confirm the presence, also of subvisual dust, at NLC and PME conditions.…”
Section: Introductionmentioning
confidence: 90%
“…It should be noted here that for a dust material density of about 2 gm cm −3 , the mass of a 1-nm dust particle is about 5000 amu. Mitchell et al (2001) from rocket experiments conducted from Norway, reported the observation of electron bite outs in the height region of 84-86 km, caused by negatively charged aerosol dust.…”
Section: Role Of Charged Dust Particlesmentioning
confidence: 99%